Danger in the reef: Proteome, toxicity, and neutralization of the venom of the olive sea snake, Aipysurus laevis. (1st December 2015) - Laustsen, Andreas H.; Gutiérrez, José María; Rasmussen, Arne R.; Engmark, Mikael; Gravlund, Peter; Sanders, Kate L.; Lohse, Brian; Lomonte, Bruno
Abstract: Four specimens of the olive sea snake, Aipysurus laevis, were collected off the coast of Western Australia, and the venom proteome was characterized and quantitatively estimated by RP-HPLC, SDS-PAGE, and MALDI-TOF-TOF analyses. A. laevis venom is remarkably simple and consists of phospholipases A2 (71.2%), three-finger toxins (3FTx; 25.3%), cysteine-rich secretory proteins (CRISP; 2.5%), and traces of a complement control module protein (CCM; 0.2%). Using a Toxicity Score, the most lethal components were determined to be short neurotoxins. Whole venom had an intravenous LD50 of 0.07 mg/kg in mice and showed a high phospholipase A2 activity, but no proteinase activity in vitro . Preclinical assessment of neutralization and ELISA immunoprofiling showed that BioCSL Sea Snake Antivenom was effective in cross-neutralizing A. laevis venom with an ED50 of 821 μg venom per mL antivenom, with a binding preference towards short neurotoxins, due to the high degree of conservation between short neurotoxins from A. laevis and Enhydrina schistosa venom. Our results point towards the possibility of developing recombinant antibodies or synthetic inhibitors against A. laevis venom due to its simplicity. Graphical abstract: Highlights: The venom proteome of the olive sea snake, Aipysurus laevis, is presented. Most abundant venom components are phospholipases A2 and short neurotoxins. Lethality screening coupled to abundance estimation identified the medically relevant toxins. BioCSL Sea Snake Antivenom neutralizes venom lethality. ICP Anti-Coral Antivenom cross-recognizes phospholipases A2 from A. laevis venom.